Sejarah Kerajaan Turki Utsmani dan Kemajuannya Bagi Dunia Islam - Muhamad Basyrul Muvid (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2022)
Abstract The purpose of this study is to analyze the history and progress of the Ottoman Turks for the Islamic World. Historically, the founder of this kingdom was a Turkic nation from the Oghuz tribe, whose name was Ertugrul, he was the pioneer of the Ottoman Empire who died in 1289 AD. Later, the leadership was continued by his son, Uthman. Uthman bin Ertugrul is considered the founder of the Ottoman empire. There are nine phases, namely the first and second phases as the pioneering and founding phases of the Ottoman Empire, phases three and four as the glory phase, phases five to 8 as the phase of stagnation, decline and dissolution of the Ottoman Empire, while the ninth phase is the phase of the Republican caliphate. Factors that influenced the glory and progress of the Ottoman Turks were political, military, economic factors, the paradigm of rulers/sultans, and socio-political factors. Meanwhile, the territory of the Ottoman Turks in parts of Asia, North Africa to Eastern Europe can be conquered and maintained for approximately 6 centuries. The heyday of Solomon (King Solomon) was known by his people as the noble title